2020
DOI: 10.1016/j.physio.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on high-level mobility in individuals with neurodegenerative disease: a systematic literature review

Abstract: Ronny (2020) The effect of exercise on high-level mobility in individuals with neurodegenerative disease: a systematic literature review. Physiotherapy, 106 pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 63 publications
(171 reference statements)
0
17
0
1
Order By: Relevance
“…That choice may include exercise that demands a high‐level of mobility such as running, trail walking or squash (Smith et al., 2019). To date, clinical trials have not commonly targeted interventions which support individuals with MS to engage in exercise that demands a high‐level of mobility (Smith, Barker, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That choice may include exercise that demands a high‐level of mobility such as running, trail walking or squash (Smith et al., 2019). To date, clinical trials have not commonly targeted interventions which support individuals with MS to engage in exercise that demands a high‐level of mobility (Smith, Barker, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, exercise interventions for individuals with MS are provided in a clinical or home-based setting where the individual follows a prescribed activity or exercise programme. High-level mobility activities such as running, sport or outdoor leisure pursuits are not typically targeted 2. Instead, exercise interventions prescribed include progressive resistance training, balance training and stationary cycling, addressing impairments such as strength and balance 3–5.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, exercise interventions prescribed include progressive resistance training, balance training and stationary cycling, addressing impairments such as strength and balance 3–5. Functional outcomes are typically focused on walking6 7 with no attention to the benefits for high-level mobility, even for those who are higher functioning 2. Benefits of participation in regular sport and exercise according to the preference of individuals with MS have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions widely comprise "Any bodily movement produced by skeletal muscles that requires energy expenditure" and any type of structured exercise (15) including gait and balance training, video-gaming (16)(17)(18) and cognitive behaviour interventions (19)(20)(21). However, although physical activities are promoted as an essential part of the clinical management across RNCs, evidence supporting physical activity interventions is still lacking in these conditions (22)(23)(24)(25)(26)(27). To date, there are significant gaps in understanding about which types of activities maintain physical functioning and increase participation in activities and quality of life across RNCs.…”
Section: Introductionmentioning
confidence: 99%
“…A second systematic review investigated the effect of exercise on high-level mobility (e.g. running or jumping) in individuals with neurodegenerative disease, such as multiple sclerosis, Parkinson's disease, HD and degenerative cerebellar disease(24). However, no new studies involving participants living with rare conditions were identified in the review, as the two intervention studies included(17,75) were reviewed in two previous systematic reviews included in the present scoping review(16,53).Outcome measuresSimilar to the interventions described in the present review, outcome measures were highly variable across the included systematic reviews and mostly assessed changes at the levels of body function (e.g.…”
mentioning
confidence: 99%